Climbing-Specific Exercise Tests: Energy System Contributions and Relationships With Sport Performance - Maciejczyk, Marcin; Michailov, Michail Lubomirov; Wiecek, Magdalena; Szymura, Jadwiga; Rokowski, Robert; Szygula, Zbigniew; Beneke, Ralph (Frontiers in Physiology, 2022)
Purpose: The aim of the study was to evaluate distinct performance indicators and energy system contributions in 4 different, new sport-specific finger flexor muscle exercise tests. Methods: The tests included a maximal strength test, the all-out test (30s) as well as the continuous and intermittent muscle endurance test at an intensity equalling 60% of maximal force, which were performed until target force could not be maintained. Gas exchange and blood lactate were measured in 13 experienced climbers during, as well as pre and post the test. The energy contribution (anaerobic alactic, anaerobic lactic and aerobic) was determined for each test. Results: The contribution of aerobic metabolism was highest during the intermittent test (59.9±12.0%). During continuous exercise, this was 28.1±15.6%, and 19.4±8.1% in the all-out test. The contribution of anaerobic alactic energy was 27.2±10.0% (intermittent), 54.2±18.3% (continuous) and 62.4±11.3% (all-out), while anaerobic lactic contribution equalled 12.9±6.4%, 17.7±8.9 and 18.2±9.9%, respectively. Conclusions: The combined analysis of performance predictors and metabolic profiles of the climbing test battery indicated that not only maximal grip force, but also all-out isometric contractions are equally decisive physical performance indices of climbing performance. Maximal grip force reflects maximal anaerobic power, while all-out average force and force time integral of constant isometric contraction at 60% of maximal force are functional measures of anaerobic capacity. Aerobic energy demand for the intermittent exercise is dominated aerobic re-phosphorylation of high energy phosphates. The force-time integral from the intermittent test was not decisive for climbing performance.